Model of Social Multiliteracy Learning: A Solution Developing Critical Thinking Skills in The 21st Century Context - Fauzi, Ghani Muhammad; Disman, Disman; Wirachman, Rony (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The purpose of this study is to describe the social multiliteracy learning model in developing critical thinking skills. This research is motivated by the importance of developing critical thinking skills in elementary school students in the context of the 21st century. This research uses literature study methods. The results showed that the steps of the social multiliteracy learning model include recognizing social phenomena, generating schemata, finding information, organizing information, elaborating and synthesizing information, summarizing key concepts and finally producing work having links with indicators of critical thinking skills namely interpretation, analysis , evaluation, explanation and inference. So it can be concluded that the social multiliteracy learning model can be one solution in developing students' critical thinking skills